Common institutional investors and supplier performance in supply chains - Cheung, Yan‐Leung; Haw, In‐Mu; Hu, Bingbing; Swink, Morgan; Zhang, Wenlan (Journal of Operations Management, 2020)
AbstractWe investigate how common institutional investors (CIIs) in supply chains affect supplier performance. Social network theory suggests that buyer–supplier relationships are influenced by networks of ties in which they are embedded. While prior research has concentrated on networks of trade interactions, we instead examine the influences of networks through common investors. Utilizing a large sample of buyer–supplier relationships, we find that the presence of CIIs improves suppliers' operating and market performance, especially for suppliers with greater dependence on buyers. In addition, supplier performance increases with the common ownership stakes held by CIIs, but decreases with the asymmetric ownership stakes of CIIs across supply chain partners. We find that better financial collaboration between the partners appears to be a mechanism through which CIIs enhance supplier performance. Lastly, we find that the role of CIIs in strengthening supplier performance is distinct from that of direct equity links. Collectively, our findings highlight a novel role of indirect cross‐ownership in fostering supply chain collaboration and coordinating vertical relationships and, in turn, improving supplier performance.